Usability Evaluation of Library Information Systems Using The System Usability Scale - Franindya Purwaningtyas (INFOKUM, 2021)
Libraries for universities play a very important role, especially in efforts to manage and disseminate information. The library information system is very helpful for the academic community in accessing everything in the library. For this reason, it is necessary to evaluate the usefulness of the library information system. One of the tools that can be used to evaluate library information systems is the System Usability Scale (SUS). This study aims to evaluate the university library information system using the SUS questionnaire. Research respondents are samples taken from students who have used library information systems. Based on the results of the questionnaire obtained a score of 70.4 with a rating of "Good" and Letter Grade "B".